2018
DOI: 10.1186/s41938-018-0080-x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and bacterial nematicides in integrated nematode management strategies

Abstract: Plant-parasitic nematodes (PPNs) pose a serious threat to quantitative and qualitative production of many economic crops worldwide. An average worldwide crop loss of 12.6% (equaled $215.77 billion) annually has been estimated due to these nematodes for only the top 20 life-sustaining crops. Due to the growing dissatisfaction with hazards of chemical nematicides, interest in microbial control of PPNs is increasing and biological nematicides are becoming an important component of environmentally friendly managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(66 citation statements)
references
References 71 publications
2
61
0
3
Order By: Relevance
“…This result was consistent with that in a previous study by Mackie et al (1999), who stated that dry conditions could restrict the expression of fungal disease, in view of the many species in the genus Paecilomyces that are pathogens (Israel et al, 2018;Piekarska, Trusz & Szczesniak, 2018). Meanwhile, some species of this genus were demonstrated as biocontrol agents, such as Paecilomyces lilacinus (Wei et al, 2015;Abd-Elgawad & Askary, 2018) and Paecilomyces fumosoroseus (Ruiu, 2018).…”
Section: Variation In Soil Fungal Community Composition Under Alfalfasupporting
confidence: 92%
“…This result was consistent with that in a previous study by Mackie et al (1999), who stated that dry conditions could restrict the expression of fungal disease, in view of the many species in the genus Paecilomyces that are pathogens (Israel et al, 2018;Piekarska, Trusz & Szczesniak, 2018). Meanwhile, some species of this genus were demonstrated as biocontrol agents, such as Paecilomyces lilacinus (Wei et al, 2015;Abd-Elgawad & Askary, 2018) and Paecilomyces fumosoroseus (Ruiu, 2018).…”
Section: Variation In Soil Fungal Community Composition Under Alfalfasupporting
confidence: 92%
“…Due to increased adverse effects of chemical nematicides and growing concerns for human health and environment, interest in biological nematicides has attracted more attention by both researchers and the agro-industry and has become an important component of eco-friendly management strategies [113][114][115]. The results of our questionnaire showed that 23% of organic farmers applied bio-nematicides for managing PPNs, specifically, Meloidogyne spp.…”
Section: Ppn Management In Organic Farming Systems Of Southern Moroccomentioning
confidence: 96%
“…Application of biological control agents and plant growth promotion is not a new concept ( Oostendorp et al., 1991 ) and has already been discussed in several comprehensive reviews ( Cross et al., 1999 ; Khan and Kim, 2007 ; Timper, 2014 ; Schouteden et al., 2015 ; Ntalli and Caboni, 2017 ; Abd-Elgawad and Askary, 2018 ; Xiang et al., 2018 ; Dutta et al., 2019 ). A number of different bacterial genera, namely Pasteuria , Pseudomonas , Burkholderia , Arthrobacter , Serratia , Achromobacter , and Rhizobium are known to have nematicidal potential.…”
Section: Biological Controlmentioning
confidence: 99%
“…General mechanisms of action involved in biocontrol fit into one of the categories as antibiotic production and/or other antagonism against PPN or induced resistance, which can vary even within a single genus. For example, in the genus Bacillus , the anti-RKN mechanism of action is based on enzymatic action for B. firmus , toxic antibiotics in B. cereus and B. subtilis , and toxic protein particles namely cry proteins in B. thuringiensis ( Abd-Elgawad and Askary, 2018 ). Application of B. cereus strain BCM2 to control M. incognita in tomato has shown that it colonized at the root exudates and worked as a second-stage juveniles (J2) repellent, resulting in reduction of the nematode damage ( Li et al., 2019 ).…”
Section: Biological Controlmentioning
confidence: 99%
See 1 more Smart Citation